Cytokine signaling by grafted neuroectodermal stem cells rescues motoneurons destined to die - Pajer Krisztián (EXPERIMENTAL NEUROLOGY, 2014)
Following an injury to their axons close to the cell body, adult motoneurons generally die. This type of injury, typically caused by avulsion of the spinal ventral root, initiates the activation of astrocytes and microglial cells and the extracellular space becomes loaded with excessive amounts of excitotoxic glutamate. We have provided evidence that, following ventral root avulsion and reimplantation, murine embryonic neuroectodermal stem cells (NE-GFP-4C) grafted into the rat spinal cord rescue the vast majority of the motoneurons that would otherwise die, and enable them to reinnervate peripheral targets. Stem cell grafts produced the modulatory cytokines IL-1-alpha, IL-6, IL-10, TNF-alpha and MIP-1-alpha, but not neurotrophic factors. The neurons and astrocytes in the ventral horn of grafted animals also produced IL-6 and MIP-1-alpha, indicating a strong interaction between the graft and the host tissue. The infusion of function-blocking antibodies against all cytokines into the grafted cords completely abolished their motoneuron-rescuing effect, while neutralization of only IL-10 suggested its strong effectivity as concerns motoneuron survival and a milder effect on reinnervation. It is suggested that, apart from the anti-inflammatory function of IL-10, the pro-inflammatory cytokines produced exert a strong modulatory function in the CNS, promoting the prevention of neuronal cell death.